2010
DOI: 10.1186/1475-2875-9-350
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of non-parasitized red blood cells in malaria: a putative mechanism involved in the pathogenesis of anaemia

Abstract: BackgroundSevere anaemia is a common complication of Plasmodium falciparum malaria in hyperendemic regions. Premature elimination of non-parasitized red blood cells (nRBC) has been considered as one mechanism involved in the genesis of severe malaria anaemia. It has been reported that apoptosis can occur in RBC and, consequently, this cell death process could contribute to anaemia. This study was performed to evaluate the susceptibility of nRBC to apoptosis in a malaria anaemia murine model.MethodsBalb/c mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 34 publications
2
50
1
Order By: Relevance
“…Clinical studies have shown both similarities and differences in the malaria pathology in humans and mice in terms of invasion characteristics and malarial anemia (20). For the scope of our study, which concerned mainly mechanical RBC filtration in spleen, Plasmodium yoelii-infected mice were chosen as our mouse model for two reasons: first, mouse spleen trapping of Plasmodium yoelii-infected RBCs was demonstrated by prior experimental studies (40), and second, similar to Plasmodium falciparum infection in humans, where the massive destruction of uninfected RBCs plays a significant role in malarial anemia, nonparasitized RBCs in Plasmodium yoelii-infected mice are also believed to contribute to murine malarial anemia (41). Additionally, it should be noted that for a typical nonsinusal spleen, adhesion (rather than deformability) is believed to be the predominant mechanism for RBC removal, as the critical mesh size of the spleen is significantly larger.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown both similarities and differences in the malaria pathology in humans and mice in terms of invasion characteristics and malarial anemia (20). For the scope of our study, which concerned mainly mechanical RBC filtration in spleen, Plasmodium yoelii-infected mice were chosen as our mouse model for two reasons: first, mouse spleen trapping of Plasmodium yoelii-infected RBCs was demonstrated by prior experimental studies (40), and second, similar to Plasmodium falciparum infection in humans, where the massive destruction of uninfected RBCs plays a significant role in malarial anemia, nonparasitized RBCs in Plasmodium yoelii-infected mice are also believed to contribute to murine malarial anemia (41). Additionally, it should be noted that for a typical nonsinusal spleen, adhesion (rather than deformability) is believed to be the predominant mechanism for RBC removal, as the critical mesh size of the spleen is significantly larger.…”
Section: Discussionmentioning
confidence: 99%
“…Although malaria parasites induce hemolysis as the result of parasite replication and subsequent rupture of the host red blood cells (RBCs), other mechanisms, such as dysregulation and/or suppression of erythropoiesis, as well as direct and indirect destruction of non-parasitized RBCs (nRBCs) have been described. 2,3 Increased levels of nRBC apoptosis, 18 accelerated senescence, 19 and accelerated destruction of nRBCs by either opsonization or complement activation [20][21][22] have also been documented as major inducers of malaria-related anemia. Additionally, micronutrient deficiencies, including iron, folate, and vitamin B12, are known to significantly contribute to malaria-related anemia.…”
Section: Introductionmentioning
confidence: 99%
“…During malaria, accelerated RBC destruction attributes to induction of apoptosis like process in uninfected RBC and development of oxidative stress [5]. Oxidative stress developed during the first hour (a sharp ROS spike by 15 min) of MetHb treatment was found to be responsible for the observed loss of membrane fragility and hemolysis (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…According to a rough estimate, during malaria every infected RBC (IRBC) causes lysis of ten or more uninfected RBC to exhibit hemolytic anemia [4]. A recent study correlates the enhanced uninfected RBC destruction through apoptosis with the observed development of anemia during malaria [5]. The mechanistic details of apoptosis in uninfected RBC or inducer molecules are not known but results indicate prooxidant molecules released from infected RBC might be responsible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation